2018
DOI: 10.1021/acs.jnatprod.8b00341
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Antimutagenic Effects of Onoceranoid-Type Triterpenoids from the Leaves of Lansium domesticum

Abstract: A methanol extract of the dried leaves of Lansium domesticum showed antimutagenic effects against 3-amino-1,4dimethyl-5H-pyrido [4,3-b]indole (Trp-P-1) and 2-amino-1-methyl-6-phenylimidazo[4,5-bI]pyridine (PhIP) using the Ames assay. Nine new onoceranoid-type triterpenoids, lansium acids I−IX (1−9), and nine known compounds (10−16) were isolated from the extract. The structures of the new compounds were elucidated on the basis of chemical and spectroscopic evidence. The absolute stereostructures of the new com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…As a result, limonin (19) and lansionic acid (53) significantly decreased the frequency of micronucleated reticulocytes (MNRETs) treated with PhIP at 24 h and 48 h after the administration ( Fig. 4) [4,7].…”
Section: Evaluation Of the Antimutagenic Effects Of Isolated Compoundmentioning
confidence: 94%
See 4 more Smart Citations
“…As a result, limonin (19) and lansionic acid (53) significantly decreased the frequency of micronucleated reticulocytes (MNRETs) treated with PhIP at 24 h and 48 h after the administration ( Fig. 4) [4,7].…”
Section: Evaluation Of the Antimutagenic Effects Of Isolated Compoundmentioning
confidence: 94%
“…Based on these studies, we searched for antimutagenic materials derived from foods. In the course of this study, we found using the Ames test that the methanolic (MeOH) extracts of C. limon [4,5], aerial parts of I. japonicus [6], and leaves of L. domesticum [7,8] showed antimutagenic effects against Trp-P-1 and PhIP. Therefore, we directed our efforts toward the isolation of their constituents and evaluation of the antimutagenic effects of the isolated constituents using the Ames test and in vivo micronucleus test.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations